Fabrication of Dye Sensitized Solar Cell Using Cassava Leaf Extract and Red Dragon Fruit - Purnomo, Teguh; Nayan, Ahmad; Sayuthi, Muhammad; Islami, Nurul; Rahman, Abdul (Universitas Merdeka Malang, 2023)
This research aims to identify the absorbance and consistency of the efficiency of DSSC (Dye-Sensitized Solar Cells). The study was conducted with variations of chlorophyll-anthocyanin mixture using different volumes of dye solutions: 10 ml of a cassava leaf and 20 ml of red dragon fruit, 20 ml of a cassava leaf and 10 ml of red dragon fruit, and 10 ml of a cassava leaf and 10 ml of red dragon fruit. The Dye-Sensitized Solar Cell system consists of natural dye as the colorant, electrolyte solution, two FTO glass substrates with dimensions of 2.5 cm x 2.5 cm, which function as working electrodes coated with titanium dioxide as the semiconductor using the doctor blade method, and counter electrode coated with carbon. All components of the Dye-Sensitized Solar Cell are arranged in a sandwich-like structure, with the counter electrode facing the working electrode and clamped together using paper clips. The highest absorbance value was obtained with the variation of 20 ml red dragon fruit and 10 ml cassava leaf compared to other mixtures. The highest efficiency and power of the Dye-Sensitized Solar Cell were also obtained with 20 ml of red dragon fruit and 10 ml of cassava leaf